Adverse Selection And Moral Hazard Effects In The Malaysian Mortgage Market. - Marashdeh, Omar (Asian Academy of Management (AAM), 1996)
Adverse selection and moral hazard arise in markets with imperfect or asymmetrical information, i.e., one party has more information than the other, such as the labour market, credit market, and insurance market. Prices in markets with imperfect information may have two effects: sorting and incentive effects (Stiglitz and Weiss, 1981). Interest rates sort customers into three groups, namely, low risk, medium risk, and high risk group. With higher interest rates, low and medium risk groups are more likely to drop out of the market. Therefore, higher interest rates act as a screening device in rationing credit and may adversely sort bad customers with high risk from good customers with low risk.